Status Hukum Wilayah Palestina Dalam Peta Digital Internasional Berdasarkan Hukum Internasional - Kesya Meidy Lourens; Arman Anwar; Richard Marsilio Waas (TATOHI: Jurnal Ilmu Hukum, 2022)
Introduction: This study discusses the issue of Palestine's non-participation in making international-based digital maps, Google in this case Google maps, as one of the Multinational or Transnational companies, which is part of the subject of International Law.Purposes of the Research: Knowing and analyzing the legal status of the Palestinian territories on international digital maps in international law. Methods of the Research: This study uses a normative juridical method with the legal materials used in the research are primary, secondary and tertiary with the use of literature study techniques in the form of international legal regulations, scientific works and literature.Results of the Research: The results of the study show that in international law, digital-based maps have not been properly regulated, so that in the process of making digital maps by digital companies under the auspices of multinational companies, there are many problems because there are no written provisions. To overcome this, it is necessary to make arrangements internationally in order to create legal certainty and prevent the emergence of public opinion which interprets unilaterally so that it can threaten the existence of a country's sovereignty.